The Treatment of Sex Offenders in Germany: The Sozialtherapie (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article aims at analyzing the treatment of sex offenders in Germany by focusing on the treatment program called Sozialtherapie. After providing a short introduction on the German sanctioning system and on the last reform of sexual offenses, the article turns to a brief analysis of the Risk-Need-Responsitivity and the Good Lives Model. Then, the treatment program of the Sozialtherapie will be analyzed in all its phases. Finally, the paper will raise some critical questions related to the use of the Sozialtherapie, with special regard to the reduction of recidivism and to its mandatory character.
Keywords: Treatment; sex offenders; Risk-Need-Responsitivity; Sozialtherapie; recidivism